Demographic, social and clinical characteristics of women in childbearing age affected by leprosy - Clodis Maria Tavares; Tâmyssa Simões Santos; Nataly Mayara Cavalcante Gomes; Reinaldo Antônio Silva-Sobrinho; Fernanda Silva Goes; Ana Maria de Almeida (Universidade Federal de Santa Maria, 2018)
Aim: to describe demographic, social and clinical characteristics of women in childbearing age affected by leprosy in a capital city in the northeast of Brazil. Method: crosssectional descriptive study, with quantitative approach. The study was composed by 217 women, resulting in an intentional sample of 60, who have attended the criteria of inclusion. Results: the data showed that 95% of the subjects were set between 20 and 49 years of age. The detection modes which presented a higher percentage were both the handling and the spontaneous demands, with 60% of the cases. It was identified that 30% were diagnosed in the dimorphic form, which is confirmed by the data regarding the multibacillary classification. Conclusion: the demographic, social and clinical characteristics were: economically active women, mostly illiterate, who are married and perform both remunerated and domestic occupations.